Race and Ethnicity, Obesity, Metabolic Health, and Risk of Cardiovascular Disease in Postmenopausal Women. Issue 5 (20th May 2015) - Schmiegelow, Michelle D.; Hedlin, Haley; Mackey, Rachel H.; Martin, Lisa W.; Vitolins, Mara Z.; Stefanick, Marcia L.; Perez, Marco V.; Allison, Matthew; Hlatky, Mark A.
Abstract : Background: It is unclear whether obesity unaccompanied by metabolic abnormalities is associated with increased cardiovascular disease risk across racial and ethnic subgroups. Methods and Results: We identified 14 364 postmenopausal women from the Women's Health Initiative who had data on fasting serum lipids and serum glucose and no history of cardiovascular disease or diabetes at baseline. We categorized women by body mass index (in kg/m 2 ) as normal weight (body mass index 18.5 to <25), overweight (body mass index 25 to <30), or obese (body mass index ≥30) and by metabolic health, defined first as the metabolic syndrome (metabolically unhealthy: ≥3 metabolic abnormalities) and second as the number of metabolic abnormalities. We used Cox proportional hazards regression to assess associations between baseline characteristics and cardiovascular risk. Over 13 years of follow‐up, 1101 women had a first cardiovascular disease event (coronary heart disease or ischemic stroke). Among black women without metabolic syndrome, overweight women had higher adjusted cardiovascular risk than normal weight women (hazard ratio [HR] 1.49), whereas among white women without metabolic syndrome, overweight women had similar risk to normal weight women (HR 0.92, interaction P =0.05). Obese black women without metabolic syndrome had higher adjusted risk (HR 1.95) than obese white women (HR 1.07; interaction P =0.02). Among women with only 2 metabolic abnormalities, cardiovascular risk was increased in black women who were overweight (HR 1.77) or obese (HR 2.17) but not in white women who were overweight (HR 0.98) or obese (HR 1.06). Overweight and obese women with ≤1 metabolic abnormality did not have increased cardiovascular risk, regardless of race or ethnicity. Conclusions: Metabolic abnormalities appeared to convey more cardiovascular risk among black women.